HUBUNGAN CITRA TUBUH TERHADAP STATUS GIZI PRAMUGARI PT. GARUDA INDONESIA PERIODE JANUARI 2014 - Sanni Rizky Putri (2014)
Women of childbearing age is a determinant of a nation's progress in carrying out reproductive function. Changes in lifestyle and diet as well as increasing business is a problem in meeting the nutritional needs for adults. Nutritional status at this age relates to the ability to perform these functions. Body image is one of the determinants of social life in the future that could affect the cause of the nutrition needs. Women were preoccupied to think of the image of her body to make it look attractive. A flight attendant job requirements and work instructions have weight proportionate and attractive appearance. The aim of this study was to acknowledge the relationship of body image to the nutritional status of a flight attendants in PT. Garuda Indonesia period January 2014. The characteristic of this study was analytical descriptive with cross-sectional design. This research was taken in PT. Garuda Indonesia Soekarno-Hatta International Airport. The sample who fulfilled the inclusive criteria was 97 people with consecutive sampling method. Data was analyzed by using Chi Square test (α=0.05) showed that there was relation between body image and body mass index of a flight attendants (p=0.005, <0.05) and there was relation between body image and lingkar lengan atas of a flight attendants (p=0.000, <0.05). For next research is recommended to research another factor like knowledge of nutrition.